Façade lighting designs in historical buildings: The case of Mersin Kızkalesi - Özcan, Gizem Nur; Akar, Tuba (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
This study discusses the illumination of cultural assets, a live topic worldwide. While any kind of lighting demands expertise, the situation becomes more sensitive in historical building lighting. The necessity of this study is due to the inadequacy of design approaches for historical building lighting, which is becoming increasingly widespread in Türkiye. Lighting examples in the world and in Türkiye are examined and positive-negative aspects identified. The examples are evaluated in terms of various criteria such as illuminance levels, colour, accents, visual order, and architectural suitability, and the necessary criteria for lighting design were established. Based on the theoretical background of the study, a lighting design process has been defined for Kızkalesi. The lighting design proposal was developed not only for touristic and architectural purposes, but also in line with basic principles such as increasing the night visibility of the cultural asset, revealing the values of the structure, and taking into account ecological sensitivities, environmental management, and light pollution. It is thought that this plan, which defines how the process should be handled from beginning to end and which experts and actors should guide the process, can also be helpful in the illumination process of other historical buildings.